The Peremptory Writ in the Code of Criminal Procedure - Bratu, Andrada Daniela (Technium Social Sciences Journal, 2023)
Criminal proceedings take place in accordance with the law. Both the summons and the transmission of documents or the peremptory writ are carried out according to the criminal procedural decisions established by the Code of Criminal Procedure. The summons, prior to the warrant to be brought, is carried out ex officio, which also implies the obligation to carry out the summons procedure. It is fundamental to carry out the summons procedure correctly and to serve other procedural documents at every stage of criminal proceedings (criminal investigation, preliminary chamber and trial), representing the official way by which the procedural subject is informed about procedural acts performed or procedural measures ordered by justice. Failure to comply with the summons and bringing process may lead to the reopening of criminal proceedings, resulting in delays in solving the case and criminal trials that do not comply with the provisions of the European Convention on Human Rights. It is essential to know the rules of procedure regarding summoning, warranting and serving documents, in order to perform a correct act in court, and in carrying out a good judicial conduct, the clerk plays a very important role, becoming a real help for the activity of a prosecutor or judge. Through the professional and competent performance of his/her duties, the Registrar also has a major role in the prompt resolution of cases.